Studies on the Flowers of Asystasia gangetica - Sethuraman*, M.G.; Vigneswari, K. (Asian Journal of Chemistry, 2010)
Fresh flowers of Asystasia gangetica (Linn) (Acanthacea) havebeen extracted with 80% ethanol. The aqueous concentrate onfractionation with various solvents yielded luteolin 7-O-neohesperidoside which has been characterised by chemical andphysical techniques. The crude aqueous extract as well as the isolatehave been investigated for the anti-inflammatory activity by in-vivoand in-vitro studies. From the results the anti-inflammatory activityof Asystasia gangetica could be correlated to the presence of luteolin7-O-neohesperidoside.